Metformin Use and Lung Cancer Risk in Diabetic Patients: A Systematic Review and Meta-Analysis - Long Yao (Disease Markers, 2019)
Background. Antidiabetic medications (ADMs) can alter the risk of different types of cancer, but the relationship between lung cancer incidence and metformin remains controversial. Our aim was to quantitatively estimate the relationship between incidences of lung cancer and metformin in patients with diabetes in this meta-analysis. Methods. We performed a search in PubMed, Embase, ISI Web of Science, and Cochrane Library until September 20, 2017. The odds ratio (OR), relative risk (RR) or hazard ratio (HR), and 95% confidence interval (95% CI) were estimated using the random-effect model. The Newcastle-Ottawa Scale (NOS) was used to assess the study quality. Results. A total of 13 studies (10 cohort studies and 3 case-control studies) were included in the meta-analysis. Compared to nonmetformin users, metformin probably decreased lung cancer incidence in diabetic patients (RR=0.89; 95% CI, 0.83-0.96; P=0.002) with significant heterogeneity (Q=35.47, I2=66%, P=0.0004). Subgroup analysis showed that cohort studies (RR=0.91; 95% CI, 0.85-0.98; P=0.008), location in Europe (RR=0.90; 95% CI, 0.86-0.94; P<0.0001), the control drug of the sulfonylurea group (RR=0.91; 95% CI, 0.86-0.96; P=0.001), and adjusting for smoking (RR=0.86; 95% CI, 0.75-1.00; P=0.05) may be related to lower lung cancer risk. No significant publication bias was detected using a funnel plot. Conclusion. Metformin use was related to a lower lung cancer risk in diabetic patients compared to nonusers, but this result was retrieved from observational studies and our findings need more well-designed RCTs to confirm the association.